Kitāb al-fayḍ bi-al-ḥaqq al-mulaqqab bi-Damgh al-bāṭil - Rafīʻuddīn Dihlavī, 1749-1818 (Idārah Nashr, wa-Ishaʻat, Madrasat Nuṣrat al-ʻUlūm, 1976)
Polemical writing on the Sufi doctrines of unity of being and unity of appearance.